Embryonal rhabdomyosarcoma of oropharynx in a 65-year-old male with indolent clinical presentation and unusual morphology. (9th November 2022) - Surucu, A; Hou, T
Abstract: Introduction/Objective: Embryonal rhabdomyosarcoma (ERMS) is a malignant primitive mesenchymal tumor which commonly affects children and adolescence. Although head and neck area is a common location for ERMS, oropharynx is rarely involved. ERMS in adults often present with stage IV disease and show a relatively poor prognosis. Loss of heterozygosity in 11p15.5 is one of the common genetic findings in sporadic ERMS. Methods/Case Report: A 65-year-old male with no significant medical history, presented with pharyngodynia and was found to have a polypoid mass originating from the pharyngeal surface of the soft palate and extends into the vallecula. He reported having this mass for a decade and having intermittent episodes of similar oropharyngeal symptoms which were usually resolved with antibiotics. Results (if a Case Study enter NA): Excisional biopsy shows a 2.4 cm polypoid mass with atypical cellular proliferation in submucosa. Tumor cells demonstrate ovoid to round nuclei and eosinophilic cytoplasm. No mitotic figure was found and Ki67 proliferation index was extremely low (<1%). Immunostains showed that the tumor cells are positive for Desmin and MyoD1. Scattered cells are positive for Myogenin. Due to the unusual clinical presentation and low proliferation activity, late onset of fetal rhabdomyoma was also considered in the differential diagnosis. The specimen was sent for chromosomal microarray which showed chromosomal gains and losses including loss of heterozygosity in chromosome 11. This finding together with cytologic atypia are mostly compatible with the diagnosis of ERMS. Post-biopsy MRI and PET-CT did not reveal any residual disease or distant metastasis. Patient has been followed up for 6 months after biopsy with no sign of recurrence. Conclusion: Our case indicates that ERMS in adult can present with an indolent clinical process and low proliferating activity. Diagnosis can be challenging in this scenario. Chromosomal microarray is a useful tool to help confirm the diagnosis.